Soothing and anti-itch effect of quercetin phytosome in human subjects: a single-blind study - Maramaldi G; Togni S; Pagin I; Giacomelli L; Cattaneo R; Eggenhöffner R; Burastero SE (Dove Medical Press, 2016)
Giada Maramaldi,1 Stefano Togni,1 Ivan Pagin,1 Luca Giacomelli,2 Roberta Cattaneo,3 Roberto Eggenhöffner,2 Samuele E Burastero4 1Indena S.p.A, Milan, 2Department of Surgical Sciences and Integrated Diagnostics, School of Medicine, Genova University, Genoa, 3Abich Srl, Verbania, 4San Raffaele Scientific Institute, Milan, ItalyBackground: We evaluated the ability of quercetin, a natural antioxidant formulated in a specific delivery system, to reduce skin inflammation induced by a variety of stimuli, including UV radiation, stimulation with a histamine solution, or contact with chemical irritants. In particular, we tested the soothing and anti-itch effect of Quercevita®, 1% cream for external use, a formulation characterized by a phospholipids-based delivery system.Patients and methods: The study was a monocentric, single blind trial that enrolled a group of 30 healthy volunteers. The back of each subject was examined to identify four quadrants with no previous skin damage or naevi that were treated in order to induce a controlled and reversible form of skin stress. The areas were treated as follows: no product; Quercevita® 1% cream, 2 mg/cm2; placebo; positive control (a commercially available topical formulation containing 1% dexchlorpheniramine).Results: Only quercetin phospholipids 1% and dexchlorpheniramine 1% achieved a significant reduction in erythema with comparable results: (–10.05% [P=0.00329] for quercetin phospholipids 1% vs –14.05% [P=0.00046] for the positive control). Moreover, quercetin phospholipids 1% and dexchlorpheniramine 1% were both associated with a significant decrease in mean wheal diameter: (–13.25% and –12.23% for dexchlorpheniramine 1%, respectively). Similar findings were reported for the other tested parameters.Conclusion: Quercetin has a skin protective effect against damage caused by a variety of insults, including UV radiation, histamine, or contact with toxic chemical compounds. Indeed, quercetin is able to reduce redness, itching, and inflammation of damaged skin; it may also help restore skin barrier function, increasing hydration, and reducing water loss.Keywords: quercetin, anti-oxidant effect, anti-inflammation, reactive oxygen species